Ternary Composite of g‐C3N4/ZnFe2O4/Fe2O3: Hydrothermal Synthesis and Enhanced Photocatalytic Performance. Issue 24 (26th June 2019) - Yang, Nannan; Hu, Pengfei; Chen, Changchun; Wang, Yifeng; Pan, Lin
Abstract: A ternary composite of g‐C3 N4 /ZnFe2 O4 /Fe2 O3 was synthesized by a hydrothermal method. Structural and optical properties of the as‐synthesized composites were characterized and the photocatalytic performances were evaluated via the degradation of Rhodamine B under visible light irradiation. Results showed that this ternary composite exhibited a higher photocatalytic activity compared to the binary ZnFe2 O4 /Fe2 O3 systems in this research. The enhanced activity could be attributed to the stepped arrangement of the band structures of its components which enabled electron transfer from g‐C3 N4 to ZnFe2 O4 then to Fe2 O3 through the potential gradient, thus facilitating the charge separation and retarding their recombination. Moreover, the g‐C3 N4 /ZnFe2 O4 /Fe2 O3 exhibited stable photochemical performance without obvious deterioration after five successive runs, while the ternary composites could be conveniently separated by using an external magnetic field, showing a promising application for the photo‐oxidative degradation of organic contaminants. Abstract : The g‐C3 N4 /ZnFe2 O4 /Fe2 O3 composites are subjected to visible‐light irradiation, the photogenerated electrons in g‐C3 N4 remain separated from holes by migrating into ZnFe2 O4 and then into Fe2 O3 along the potential gradient and those generated in ZnFe2 O4 also remain separated, thus facilitating the charge separation and retarding their recombination. This is similar to the case in ZnFe2 O4 /Fe2 O3 composites. Hence, ternary composites are cost‐effective and exhibit good photocatalytic activity.